Lembaga Pembiayaan Pendidikan dalam Mewujudkan Pendidikan yang Inklusif dan Berkelanjutan di Indonesia - Ritonga, Matnur; Bariyah, Oneng Nurul; Febriansyah, Muhammad Raihan; Susanti, Dwi Kartika; Islamiati, Siti Hadiyanti Dini; Hamzah, Voullin; Lestari, Ayu (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
The role of educational financing institutions is crucial in supporting inclusive and sustainable education in Indonesia, which is in line with the mandate of the 1945 Constitution that guarantees every citizen's right to education. This study employs qualitative methods through policy analysis and case studies to evaluate the effectiveness of various financing programs, such as the Indonesia Smart Card Program, in enhancing educational access for underprivileged communities. The findings indicate that government and private educational financing institutions have significantly reduced dropout rates and increased educational participation. However, challenges remain regarding equitable quality and sustainable educational financing. Furthermore, collaboration between the public and private sectors is emphasized to create a more inclusive financing system. This research underscores that educational financing institutions play a vital role in realizing a better national education vision and must continuously adapt to existing challenges to achieve these goals.